2020
DOI: 10.1002/tox.22985
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic oxidative stress, DNA damage and apoptosis in adult zebrafish following sub‐chronic exposure to BDE‐47 and BDE‐153

Abstract: Polybrominated diphenyl ethers (PBDEs) are ubiquitous and prolific contaminant in both the abiotic and biotic environment because of the wide industrial applications of these chemicals. In the present study, the effects of 2,2 0 ,4,4 0-tetrabrominateddiphenyl ether (BDE-47) and 2,2 0 ,4,4 0 ,5,5 0-hexabromodiphenyl ether (BDE-153) exposure on the induction of hepatic oxidative stress, DNA damage, and the expression of apoptosis-related genes in adult zebrafish were investigated. The activities of antioxidant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Similar to the PS exposure groups, BDE-47 exposure significantly increased oxygen consumption rate compared to control zebrafish (eleuthero)embryos. As previously discussed for PS, this may reflect higher energetic cost linked to detoxification and ROS buffering responses, as robust BDE-47 induced oxidative stress has been reported in a variety of species including (developing) zebrafish (Fernie et al, 2005;Shao et al, 2008;Tagliaferri et al, 2010;Costa et al, 2015;Usenko et al, 2015;Meng et al, 2020;Messina et al, 2020). Again, similar to described PS mode of actions, BDE-47 and its hydroxylated metabolite 6-OH BDE-47, have recently been described to decrease mitochondrial OXPHOS gene expression and ATP production and increase oxygen consumption indicative of OXPHOS disruption uncoupling in zebrafish (Legradi et al, 2017;Zhuang et al, 2020), suggesting a mitochondrial contribution to the observed increase in oxygen consumption rate.…”
Section: Individual Ps Nanoplastic and Bde-47 Exposure Induces Organi...mentioning
confidence: 83%
See 1 more Smart Citation
“…Similar to the PS exposure groups, BDE-47 exposure significantly increased oxygen consumption rate compared to control zebrafish (eleuthero)embryos. As previously discussed for PS, this may reflect higher energetic cost linked to detoxification and ROS buffering responses, as robust BDE-47 induced oxidative stress has been reported in a variety of species including (developing) zebrafish (Fernie et al, 2005;Shao et al, 2008;Tagliaferri et al, 2010;Costa et al, 2015;Usenko et al, 2015;Meng et al, 2020;Messina et al, 2020). Again, similar to described PS mode of actions, BDE-47 and its hydroxylated metabolite 6-OH BDE-47, have recently been described to decrease mitochondrial OXPHOS gene expression and ATP production and increase oxygen consumption indicative of OXPHOS disruption uncoupling in zebrafish (Legradi et al, 2017;Zhuang et al, 2020), suggesting a mitochondrial contribution to the observed increase in oxygen consumption rate.…”
Section: Individual Ps Nanoplastic and Bde-47 Exposure Induces Organi...mentioning
confidence: 83%
“…BDE-47 may promote zebrafish feed-intake as compensatory consequences of decreased nutrient absorption or mitochondrial function, or directly via disruption of central feeding circuits. The concomitant increase in oxygen consumption rate in response to BDE-47 exposure suggests that increased feeding rates may represent a homeostatic response to provide oxidizable fuel for energetically costly detoxification or mitochondria-derived ROS buffering processes widely reported for BDE-47 ( Fernie et al, 2005 ; Shao et al, 2008 ; Tagliaferri et al, 2010 ; Costa et al, 2015 ; Usenko et al, 2015 ; Meng et al, 2020 ; Messina et al, 2020 ). However, possible directly inhibitory effects of BDE-47 on nutrient absorption and/or central suppression on feed-intake may represent alternative modes of action.…”
Section: Discussionmentioning
confidence: 98%
“…However, PBDE metabolism should result in hydroxylated products that might increase the potential for biological reactivity. Indeed, recent literature has shown that exposure to BDE-47 induced excessive ROS production in zebrafish embryos [ 61 ], increased the SOD and CAT activities in adult zebrafish liver [ 62 ], generated oxidative stress, and increased the defense system activity in adult zebrafish ovary, with significantly higher SOD activity and greater levels of malondialdehyde, one of the most significant membrane lipid peroxidation end products [ 16 ]. Moreover, Wang et al [ 63 ] observed that exposure to low BDE-47 concentrations at 96 hpf caused the SOD, CAT, and GPx activities and malondialdehyde levels to be upregulated because ROS were overproduced in zebrafish larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is an essential organ for metabolic detoxification and is sensitive to environmental toxicants. Hence, the liver is susceptible to injury when exposed to xenobiotics [26,34,35]. For instance, significant liver weight increase and cell swelling, coupled with an elevated expression of cytochrome P450 (CYP1A2, CYP3A1, and CYP2B1) enzymes and genes and hepatocytic fatty degeneration, have been reported in PBDEs (the structures are shown in Figure 1) treated animals [36][37][38][39][40][41].…”
Section: Liver Toxicitymentioning
confidence: 97%
“…PBDEs are ubiquitous toxicants frequently detected in human tissues [25]. As an essential organ for the metabolism of exogenous compounds, the liver serves as the main target for PBDEs [26,27]. For instance, the transplacental transfer of PBDEs from mother to fetus leads to tissue accumulation in the fetal liver [28].…”
Section: Introductionmentioning
confidence: 99%